Green Supplier Selection via an Integrated Multi-Attribute Decision Making Approach - Huseyin Selcuk Kilic; Ahmet Selcuk Yalcin (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The environmental awareness of society and theglobal competition market has increased significantly due to the environmentalproblems that happen today. Companies have recognized the importance offocusing on environmental issues in order to be strong in a modern competitivebusiness environment. Therefore, environmental factors are taken intoconsideration during the supplier selection process, which is an importantdecision point in the supply chain. In this study, two robust multi-attributedecision making techniques, Intuitionistic Fuzzy AHP (IF-AHP) and PROMETHEE,are used in an integrated way to better handle this selection problem. The stepsare clearly explained in the proposed methodology. First, the relative weightsof the criteria are determined by IF-AHP, which allows decision makers (DMs) todeal with the uncertainty of the evaluation process. Subsequently, the weightsof criteria obtained are used in the PROMETHEE method for the best ranking ofalternative suppliers. An application is performed in the air filtrationindustry to demonstrate the validity of the proposed method.